Methods in single phase to ground faults on power distribution systems - Soomro, Dur Muhammad; Tawafan, Adnan Hasan; Jabbar, Feryal Ibrahim (Medwell Publications, 2019)
This study highlights the main contributions for the single phase to ground faults on distribution networks field throughout a last three decades from classic methods to heuristic methods. The surveys about 76 papers that are published in the field, the quantity of existing methods for each method is determined and categorized. The study includes graphs and tables explaining the frequency of each single phase to ground faults methods and so that, researchers in the same field can be used this paper as a guideline for their research.